“Pisar o toré” ... : a saga do Mestre Roque e do povo indígena Tuxá Setsor Bragagá de Pirapora/Buritizeiro - MG na luta pela manutenção de sua identidade e território - Reginaldo Cordeiro dos Santos Junior (2024)
In this thesis I ethnographise the Tuxá Setsor Bragagá Indigenous People, located in Pirapora, Minas Gerais. In order to understand this choice, it is necessary to consider my autobiographical account, especially with regard to my experience as a civil servant for the Minas Gerais State Government between 2015 and 2018. It was through this activity that I had the opportunity to meet the Tuxá Setsor Bragagá family. It is from this initial autoethnographic approach that I present the ethnography of the Tuxá Setsor Bragagá people, with a focus on the group's ancestor, Mestre Roque Moisés Tuxá, the cornerstone for triggering the territorialisation of the Tuxá group, in a "social reorganisation" (Oliveira, 2004, p. 22). I present the biographical narrative about Mestre Roque Tuxá, based on "historical situations" (Oliveira, 2015) experienced by his people, captured in the context of research and living with the Tuxá Setsor Bragagá family, understanding this context of various events ranging from my time in the Minas Gerais State Government to my more recent experiences with the group. The concept of narrative involves the idea of a certain structuring of events in a logical and more or less chronological sequence, where characters are introduced, scenarios are established, and a plot unfolds. In this sense, the biographical narrative contributes, along the lines of Chimamanda Ngozi Adichie (2009), to removing the "danger of a single story." The danger of a homogenising history that contributes to strengthening the idea of the autochthonous illusion in which ethnic and identity rights are "guaranteed" only to collectivities that have a culture frozen in time. By combining ethnographic pieces, I present an ethnohistorical and anthropological picture of the saga of Mestre Roque Tuxá and his people. The main objective of this thesis is to highlight the figure of Mestre Roque in the hall of those who contributed to the construction of the Brazils within this Brazil of continental territorial dimension. The idea is to remove the figure of Mestre Roque and his Setsor Bragagá family from the historical anonymity imposed by the colonialist ideology that still prevails today. The main thrust of the biographical narrative presented here is to break this paradigm.